Matkaopas lapsuuden historian tutkimukseen Monitieteisiä näkökulmia ja menetelmiä - Vehkalahti, Kaisa; Jouhki, Essi; Lipkin, Sanna; Sitomaniemi-San, Johanna; Kuokkanen, Tiina (Historiallisia Tutkimuksia, 2022)
This edited volume is a handbook of research methodologies for the history of childhood. The history of childhood is a vibrant, multidisciplinary field that incorporates a rich variety of methodological approaches developed in disciplines across the social sciences and humanities, including archaeology, education, ethnology, literature, and history. The volume presents a collection of chapters that engage a range of different research traditions and employ different research material, conceptual tools, and methods of analysis for the historical study of childhood. In doing so, the volume attends to issues specific to the study of children and childhood, such as those related to research ethics and the theoretical complexities of defining 'the child' and 'childhood'. While the central focus is on the history of childhood in Finland, the volume also includes international and transnational cases, contexts, and perspectives.